Effect of Trade Liberalization on Performance of Sugar Firms in Kenya: The Case of GovernmentOwned Firms - Owiye, Peter O.; Naibei, Isaac K.; Momanyi, Gideon (European Scientific Journal, ESJ, 2016)
This study focused on the Kenyan sugar industry in the changing Kenyan business environment. The study sought to establish why Kenyan sugar firms were finding it increasingly difficult to compete within the changing Kenyan business environment. The specific objectives of the study were: one, to establish factors undermining the competitiveness of the local sugar firms; two, to find out if the local sugar firms were making any strategic responses in reaction to the changing Kenyan business environment; and three, to identify what company managers and other stakeholders consider as important measures that need to be undertaken to enhance the competitiveness of government-owned sugar firms. This study involved all the government-owned sugar in Kenya. The study found out that Kenyan sugar firms were facing very stiff competition from imported sugar. As such, local sugar firms are reported to be seriously negatively affected currently. A number of factors were found to be undermining the competitiveness of local sugar firms: competition from imported sugar, inferior production facilities, and poor management of company resources, among others. This study points at a number of strategic measures that the local sugar should put in place in response to the changes currently taking place in the Kenyan business environment; Employee retrenchment, improvement in production efficiency, sub-contracting of services considered to be subsidiary to core functions, and increased marketing activities, are some of the prominently cited strategic measures being undertaken by local sugar firms in response to the changing Kenyan business environment.